School without Party, neoliberalism and conservatism: tracking points of intersection (Práxis Educativa, 2020)
Discussions around the School without a Party movement (Escola sem Partido) have intensified the struggles for Brazilian education in recent years. Given the importance of this debate, we would like to explore in this article a small part of a research developed in the Master’s Degree, but with a focus on other aspects. Thus, we seek to describe statements present in a given discursive formation produced by the movement. To that end, we used the theoretical and methodological tools offered by the French philosopher and historian Michel Foucault. The results point to the existence of statements that revitalize neoliberal and conservative ideas in the field of Brazilian education.Keywords: School without a Party. Conservatism. Neoliberalism.